ANALYSIS OF EXAMINATIONS CONDUCTED IN CASES OF SUICIDE IN ANDIJAN REGION IN 2024 (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
According to the World Health Organization (WHO), suicide occupies one of the leading places among the causes of global mortality. Suicide is one of the leading causes of death, second only to cardiovascular diseases, cancer, and road accidents. Globally, it is one of the most common causes of death among young people and the working-age population. According to WHO data, approximately 800,000 people worldwide commit suicide each year. This means that every 40 seconds one person has to commit suicide. In the last 5 years, approximately 4 million people may have died from suicide. In high-income countries, suicide occupies a high place among the causes of death. 79% of suicides occur in low- and middle-income countries. Suicide is the third leading cause of death among adolescents aged 15-19 in the world. According to WHO data for 2023, suicide is one of the top 10 causes of death in the world. Among those aged 15-29, it is among the top 4 leading causes of death. To reduce suicide rates, the WHO recommends a number of measures, including data collection and monitoring, organizing events in educational institutions, reducing alcohol and drug use among the population, training medical workers, etc. The results of the examination of corpses in cases of suicide in the Andijan region in 2024 are presented. In 2024, the region's population reached 3,394,000, of which suicide fatalities constituted 0.003% of the total population. During the current year, the Andijan branch of the Republican Scientific and Practical Center for Forensic Medical Examination conducted 791 examinations of corpses, of which 117 cases of suicide were recorded. Most of them died from suicide - hanging. Men accounted for two-thirds of the cases. By region, the incidence of suicide per 100,000 population was higher in the Bulakbashi (6.6%), Andijan (5.3%), Shakhrikhan (5.3%), and Jalakuduk (5.0%) districts of the region compared to other districts.